MO798ORAL CALCITRIOL USE, VERTEBRAL FRACTURES AND VASCULAR CALCIFICATION IN HEMODIALYSIS PATIENTS: RESULTS FROM VITAMIN K ITALIAN (VIKI) STUDY. (29th May 2021) - Fusaro, Maria; Aghi, Andrea; Politi, Cristina; Nickolas, Thomas; Cianciolo, Giuseppe; La Manna, Gaetano; Gasperoni, Lorenzo; Mereu, Maria Cristina; Gallieni, Maurizio; Ravera, Maura; Giannini, Sandro; Sella, Stefania; et al.
Abstract: Background and Aims: In patients with Chronic Kidney Disease (CKD) mineral, bone, and calcific cardiovascular abnormalities are associated to adverse clinical outcomes, including fractures, cardiovascular events and mortality. Vitamin D hormonal system along with alteration levels that occur in calcium, phosphate, PTH, FGF23/Klotho are the main responsible of the bone and vascular metabolism changes, particularly in hemodialysis (HD) patients that experienced the very negative clinical consequences (decreased bone mass, increased fragility fractures and vascular calcification). In the setting of a comparative effectiveness study, we investigated the effect of oral calcitriol on fractures in HD patients taking into account a series of potential confounders. Method: We conducted a secondary analysis of the VIKI database, a cross-sectional study involving 387 HD patients from 18 Italian dialysis centers. Routine biochemistry and bone biochemical markers such as vitamin K levels, VKDPs, vitamin 25(OH)D, ALP, PTH, Ca, P, osteocalcin (BGP), Matrix Gla Protein (MGP) were assessed. The presence of Vertebral Fractures (VF) and Vascular Calcification (VC) was determined through spine radiograph. Reduction of >20% of vertebral body height was considered a VF. The severity of the vertebral fractures was estimated as mild, moderate and severe (reduction: 20-25%, 25-40% or >40%, respectively). VC were quantified by measuring the length of calcific deposits along the arteries (mild 0, 1-5 cm, moderate 5, 1-10 cm and severe >10 cm). Results: 177 out 387 patients (45.7%) were treated with oral calcitriol. Oral calcitriol-treated and untreated patients did not differ as for Ca, P, PTH, Albumin, BGP, MGP, and ALP. The prevalence of VF was significantly lower in patients receiving oral calcitriol than in those untreated (48.6% vs 61%, P=0.015), whereas the presence of aortic and iliac calcifications was similar between the two groups (aortic: 81.9% vs 79.5% respectively, P=0.552; iliac: 52.0% and 59.5%, P=0.167). No significant between-groups differences were observed in terms of calcification severity. In a multivariable logistic regression analysis, after adjustment for all potential confounders, oral calcitriol was associated with a marked reduction (-40.2%) of the odds of fractures (OR: 0.598, 95% CI: 0.363-0.985, P=0.043) (see Table ). Conclusion: A significant association was found between oral calcitriol and lower VF rate in HD patients. Such an effect remained significant also after data adjustment for a large series of potential confounders. Further prospective and interventional studies are needed to confirm these findings.